Functional aesthetics in industrial products (Journal of the College of Basic Education, 2022)
The values of functional beauty are a conceptual mental dimension that differs completely from the formal dimension, as beauty considerations in this aspect are added by the user, and the designer intends to include them in the products as internal content that the recipient perceives through his interaction with the product, and through what he derives from it in terms of interest and benefit. On the material and moral levels. In this dimension (functional beauty), we are trying to lay objective foundations for judgments of taste in this field. As the concept of functional beauty is defined as: "The union of strength with simplicity in creativity, which is the key in developing products that help the user to be freed from the constraints of the external logic of products towards a "creative symbiosis" between the user and the activities of the product. Industrial products are defined as "things that, through their properties, give pleasure to man, in one way or another."